Isolation and characterization of bacteria from burn-injured patients and detection of their antibiotic sensitivity pattern - Tanzin, Dewan; Binte Farooq, Faria; Zahedy, Syeda Fairuz; Baidya, Purbita; Brinto, Tamanna Tisha; Mim, Mahsina Moshiat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.